Preparation process of high-capacity hydrogen storage alloy material
By precisely controlling the smelting and heat treatment process, the uneven distribution of components and impurities of alloy hydrogen storage materials are solved, the hydrogen storage performance and cycle stability are improved, and the preparation of high-capacity hydrogen storage materials is realized. It is suitable for the fields of hydrogen energy storage and conversion .
Patent Information
- Application Number
- CN202411200871.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
The traditional alloy hydrogen storage material preparation method has problems such as uneven component distribution, high impurity content and limited hydrogen storage performance, which limits its wide application in hydrogen energy storage and conversion.
By precisely controlling the smelting and heat treatment process, we ensure the uniform distribution of alloy components and the removal of impurities. We use specific proportional raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt to carry out high-temperature smelting and water-cooling with argon protection. The copper roller is quickly cooled, combined with heat treatment to stabilize the crystal phase structure and improve hydrogen storage performance.
It significantly improves the hydrogen storage capacity and cycle stability of the alloy, enhances the hydrogen absorption and discharge rate, and ensures the high performance of the product and the controllability and stability of large-scale production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage alloys, and specifically relates to a preparation process of a high-capacity hydrogen storage alloy material. Background Art
[0002] In the field of alloy hydrogen storage materials, although there are many preparation methods, traditional methods often have problems such as uneven component distribution, high impurity content, and limited hydrogen storage performance, which limit their wide application in hydrogen energy storage and conversion. With the rapid development of the hydrogen energy industry, the demand for high-performance, long-life, and low-cost hydrogen storage materials is becoming increasingly urgent. Therefore, how to optimize the preparation method of alloy hydrogen storage materials to improve their hydrogen storage capacity, cycle stability, and production efficiency has become a technical problem that needs to be solved urgently. In this context, this paper proposes an innovative method for preparing alloy hydrogen storage materials, which aims to overcome the shortcomings of existing technologies and achieve a comprehensive improvement in the performance of alloy hydrogen storage materials by precisely controlling the smelting and heat treatment processes. Summary of the invention
[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a process for preparing a high-capacity hydrogen storage alloy material, which effectively solves the problems raised by the background technology.
[0004] To achieve the above object, the present invention provides the following technical solution: a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0005] Step 1: Raw material preparation:
[0006] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0007] Step 2: Pre-smelting treatment:
[0008] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0009] Step 3: High temperature smelting:
[0010] Set the melting program, first raise the temperature to 120-150℃, keep the temperature constant for 10-15 minutes, then continue to raise the temperature to 800-850℃, keep the temperature constant for 5-10 minutes to remove low-boiling volatiles; finally raise the temperature to 1650-1750℃, keep the temperature constant for 20-30 minutes to ensure that the raw materials are completely melted and mixed evenly.
[0011] Step 4: Casting and cooling:
[0012] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0013] Step 5: Heat treatment:
[0014] The crushed alloy particles are placed in a heat treatment furnace, heated to 850-920°C, kept constant for 5-10 minutes, and then slowly cooled to room temperature at a rate of 20-50°C / min; this step helps stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance.
[0015] Step 6: Product testing:
[0016] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0017] Preferably, the specific weight ratio of the raw materials in step one is: nickel (40-50 parts), samarium (5-8 parts), magnesium (15-20 parts), aluminum (10-15 parts), cerium (3-5 parts), manganese (5-7 parts), lanthanum (5-10 parts), and cobalt (3-5 parts).
[0018] Preferably, the specific weight ratio of the raw materials in step one is: nickel (42-48 parts), samarium (6-7 parts), magnesium (16-18 parts), aluminum (12-14 parts), cerium (3-4 parts), manganese (6-7 parts), lanthanum (6-8 parts), and cobalt (3-4 parts).
[0019] Preferably, the specific weight ratio of the raw materials in step one is: nickel (45 parts), samarium (6 parts), magnesium (17 parts), aluminum (13 parts), cerium (4 parts), manganese (6 parts), lanthanum (7 parts), and cobalt (3 parts).
[0020] Preferably, the vacuum is evacuated in step 2 until the pressure in the reaction furnace does not exceed 10 Pa, and then high-purity argon (≥99.999%) is filled in to keep the pressure in the furnace at 0.02-0.03 MPa.
[0021] Preferably, the particle size of the crushed particles in step 4 is less than 150-200 mesh.
[0022] Preferably, in step five, the crushed alloy particles are placed in a heat treatment furnace, the temperature is raised to 900° C., maintained at the constant temperature for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] By precisely controlling the smelting and heat treatment processes, the uniform distribution of alloy components and the effective removal of impurities are ensured, significantly improving the hydrogen storage capacity and cycle stability of the alloy; at the same time, the optimized crystal phase structure further enhances the hydrogen absorption and desorption rate of the alloy, enabling it to exhibit excellent performance in the field of hydrogen energy storage and conversion; in addition, the controllability of the process provides a solid foundation for large-scale production and ensures the stability and consistency of product quality. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The present invention relates to a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0027] Step 1: Raw material preparation:
[0028] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0029] Step 2: Pre-smelting treatment:
[0030] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0031] Step 3: High temperature smelting:
[0032] Set the melting program, first raise the temperature to 120-150℃, keep the temperature constant for 10-15 minutes, then continue to raise the temperature to 800-850℃, keep the temperature constant for 5-10 minutes to remove low-boiling volatiles; finally raise the temperature to 1650-1750℃, keep the temperature constant for 20-30 minutes to ensure that the raw materials are completely melted and mixed evenly.
[0033] Step 4: Casting and cooling:
[0034] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0035] Step 5: Heat treatment:
[0036] The crushed alloy particles are placed in a heat treatment furnace, heated to 850-920°C, kept constant for 5-10 minutes, and then slowly cooled to room temperature at a rate of 20-50°C / min; this step helps stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance.
[0037] Step 6: Product testing:
[0038] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0039] The specific weight ratio of the raw materials in step 1 is: nickel (40-50 parts), samarium (5-8 parts), magnesium (15-20 parts), aluminum (10-15 parts), cerium (3-5 parts), manganese (5-7 parts), lanthanum (5-10 parts), and cobalt (3-5 parts).
[0040] The specific weight ratio of the raw materials in step 1 is: nickel (42-48 parts), samarium (6-7 parts), magnesium (16-18 parts), aluminum (12-14 parts), cerium (3-4 parts), manganese (6-7 parts), lanthanum (6-8 parts), and cobalt (3-4 parts).
[0041] The specific weight ratio of the raw materials in step 1 is: nickel (45 parts), samarium (6 parts), magnesium (17 parts), aluminum (13 parts), cerium (4 parts), manganese (6 parts), lanthanum (7 parts), and cobalt (3 parts).
[0042] The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10Pa, and then high-purity argon (≥99.999%) is filled to maintain the pressure in the furnace at 0.02-0.03MPa.
[0043] The particle size of the crushed particles in step 4 is less than 150-200 mesh.
[0044] In the step 5, the crushed alloy particles are placed in a heat treatment furnace, heated to 900° C., kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
[0045] Embodiment 1:
[0046] The present invention relates to a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0047] Step 1: Raw material preparation:
[0048] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0049] Step 2: Pre-smelting treatment:
[0050] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0051] Step 3: High temperature smelting:
[0052] Set the melting program, first raise the temperature to 120℃ and keep it constant for 15 minutes, then continue to raise the temperature to 850℃ and keep it constant for 10 minutes to remove low-boiling volatiles; finally raise the temperature to 1750℃ and keep it constant for 20 minutes to ensure that the raw materials are completely melted and mixed evenly.
[0053] Step 4: Casting and cooling:
[0054] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0055] Step 5: Heat treatment:
[0056] The crushed alloy particles are placed in a heat treatment furnace, heated to 850°C, kept constant for 10 minutes, and then slowly cooled to room temperature at a rate of 20°C / min; this step helps to stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance.
[0057] Step 6: Product testing:
[0058] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0059] The specific weight ratio of the raw materials in step 1 is: nickel (40 parts), samarium (5 parts), magnesium (15 parts), aluminum (10 parts), cerium (3 parts), manganese (5 parts), lanthanum (5 parts), and cobalt (3 parts).
[0060] The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10 Pa, and then high-purity argon gas (≥99.999%) is filled in to keep the pressure in the furnace at 0.02 MPa.
[0061] The particle size of the crushed particles in step 4 is 150 mesh.
[0062] Embodiment 2:
[0063] The present invention relates to a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0064] Step 1: Raw material preparation:
[0065] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0066] Step 2: Pre-smelting treatment:
[0067] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0068] Step 3: High temperature smelting:
[0069] Set the melting program, first raise the temperature to 150℃ and keep it constant for 10 minutes, then continue to raise the temperature to 800℃ and keep it constant for 10 minutes to remove low-boiling volatiles; finally raise the temperature to 1650℃ and keep it constant for 30 minutes to ensure that the raw materials are completely melted and mixed evenly.
[0070] Step 4: Casting and cooling:
[0071] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0072] Step 5: Heat treatment:
[0073] The crushed alloy particles are placed in a heat treatment furnace, heated to 920°C, kept constant for 5 minutes, and then slowly cooled to room temperature at a rate of 20°C / min; this step helps to stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance.
[0074] Step 6: Product testing:
[0075] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0076] The specific weight ratio of the raw materials in step 1 is: nickel (50 parts), samarium (8 parts), magnesium (20 parts), aluminum (15 parts), cerium (5 parts), manganese (7 parts), lanthanum (10 parts), and cobalt (5 parts).
[0077] The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10 Pa, and then high-purity argon gas (≥99.999%) is filled in to maintain the pressure in the furnace at 0.03 MPa.
[0078] The particle size of the crushed particles in step 4 is 200 mesh.
[0079] In the step 5, the crushed alloy particles are placed in a heat treatment furnace, heated to 900° C., kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
[0080] Embodiment 3:
[0081] The present invention relates to a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0082] Step 1: Raw material preparation:
[0083] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0084] Step 2: Pre-smelting treatment:
[0085] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0086] Step 3: High temperature smelting:
[0087] The melting program was set up, first the temperature was raised to 130°C and kept constant for 13 minutes, then the temperature was raised to 830°C and kept constant for 7 minutes to remove low-boiling volatiles; finally the temperature was raised to 1700°C and kept constant for 25 minutes to ensure that the raw materials were completely melted and mixed evenly.
[0088] Step 4: Casting and cooling:
[0089] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0090] Step 5: Heat treatment:
[0091] The crushed alloy particles are placed in a heat treatment furnace, heated to 900°C, kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 40°C / min; this step helps to stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance.
[0092] Step 6: Product testing:
[0093] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0094] The specific weight ratio of the raw materials in step 1 is: nickel (42 parts), samarium (6 parts), magnesium (16 parts), aluminum (12 parts), cerium (3 parts), manganese (6 parts), lanthanum (6 parts), and cobalt (3 parts).
[0095] The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10 Pa, and then high-purity argon gas (≥99.999%) is filled in to keep the pressure in the furnace at 0.02 MPa.
[0096] The particle size of the crushed particles in step 4 is 200 mesh.
[0097] In the step 5, the crushed alloy particles are placed in a heat treatment furnace, heated to 900° C., kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
[0098] Embodiment 4:
[0099] The present invention relates to a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0100] Step 1: Raw material preparation:
[0101] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0102] Step 2: Pre-smelting treatment:
[0103] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0104] Step 3: High temperature smelting:
[0105] Set the melting program, first raise the temperature to 120℃ and keep it constant for 10 minutes, then continue to raise the temperature to 800℃ and keep it constant for 5 minutes to remove low-boiling volatiles; finally raise the temperature to 1650℃ and keep it constant for 20 minutes to ensure that the raw materials are completely melted and mixed evenly.
[0106] Step 4: Casting and cooling:
[0107] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0108] Step 5: Heat treatment:
[0109] The crushed alloy particles are placed in a heat treatment furnace, heated to 850°C, kept constant for 5 minutes, and then slowly cooled to room temperature at a rate of 20°C / min; this step helps to stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance.
[0110] Step 6: Product testing:
[0111] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0112] The specific weight ratio of the raw materials in step 1 is: nickel (48 parts), samarium (7 parts), magnesium (18 parts), aluminum (14 parts), cerium (4 parts), manganese (7 parts), lanthanum (8 parts), and cobalt (4 parts).
[0113] The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10 Pa, and then high-purity argon gas (≥99.999%) is filled in to keep the pressure in the furnace at 0.02 MPa.
[0114] The particle size of the crushed particles in step 4 is 200 mesh.
[0115] In the step 5, the crushed alloy particles are placed in a heat treatment furnace, heated to 900° C., kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
[0116] Embodiment 5:
[0117] The present invention relates to a process for preparing a high-capacity hydrogen storage alloy material, comprising the following steps:
[0118] Step 1: Raw material preparation:
[0119] Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy.
[0120] Step 2: Pre-smelting treatment:
[0121] The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment.
[0122] Step 3: High temperature smelting:
[0123] Set the melting program, first raise the temperature to 150℃ and keep it constant for 15 minutes, then continue to raise the temperature to 850℃ and keep it constant for 10 minutes to remove low-boiling volatiles; finally raise the temperature to 1750℃ and keep it constant for 30 minutes to ensure that the raw materials are completely melted and mixed evenly.
[0124] Step 4: Casting and cooling:
[0125] The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency.
[0126] Step 5: Heat treatment:
[0127] The crushed alloy particles are placed in a heat treatment furnace, heated to 920°C, kept constant for 10 minutes, and then slowly cooled to room temperature at a rate of 50°C / min; this step helps to stabilize the crystal structure of the alloy and improve the hydrogen storage performance.
[0128] Step 6: Product testing:
[0129] The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
[0130] The specific weight ratio of the raw materials in step 1 is: nickel (45 parts), samarium (6 parts), magnesium (17 parts), aluminum (13 parts), cerium (4 parts), manganese (6 parts), lanthanum (7 parts), and cobalt (3 parts).
[0131] The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10 Pa, and then high-purity argon gas (≥99.999%) is filled in to keep the pressure in the furnace at 0.02 MPa.
[0132] The particle size of the crushed particles in step 4 is 200 mesh.
[0133] In the step 5, the crushed alloy particles are placed in a heat treatment furnace, heated to 900° C., kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
[0134] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0135] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A process for preparing a high-capacity hydrogen storage alloy material. It is characterized in that The following steps are involved: Step 1: Raw material preparation: Accurately weigh the raw materials of nickel, samarium, magnesium, aluminum, cerium, manganese, lanthanum and cobalt according to the ratio; ensure that the purity of all raw materials meets the requirements to reduce the impact of impurities on the properties of the alloy. Step 2: Pre-smelting treatment: The weighed raw materials are placed in a crucible with argon protection to avoid oxidation; after evacuation, inert gas is filled in to provide an inert gas protection environment. Step 3: High temperature smelting: Set the melting program, first raise the temperature to 120-150℃, keep the temperature constant for 10-15 minutes, then continue to raise the temperature to 800-850℃, keep the temperature constant for 5-10 minutes to remove low-boiling volatiles; finally raise the temperature to 1650-1750℃, keep the temperature constant for 20-30 minutes to ensure that the raw materials are completely melted and mixed evenly. Step 4: Casting and cooling: The melt is cast into a preheated mold under argon protection and quickly cooled by a water-cooled copper roller to obtain alloy flakes or blocks; the cooled alloy needs to be further crushed to obtain the required particle size to ensure good electrochemical properties and hydrogen absorption and desorption efficiency. Step 5: Heat treatment: The crushed alloy particles are placed in a heat treatment furnace, heated to 850-920°C, kept constant for 5-10 minutes, and then slowly cooled to room temperature at a rate of 20-50°C / min; this step helps stabilize the crystal phase structure of the alloy and improve the hydrogen storage performance. Step 6: Product testing: The prepared alloy hydrogen storage material is subjected to performance tests, including hydrogen storage capacity, hydrogen absorption and desorption rate, and cycle stability, to ensure that the product meets the design requirements.
2. A process for preparing a high-capacity hydrogen storage alloy material according to claim 1, It is characterized in that The specific weight ratio of the raw materials in step 1 is: nickel (40-50 parts), samarium (5-8 parts), magnesium (15-20 parts), aluminum (10-15 parts), cerium (3-5 parts), manganese (5-7 parts), lanthanum (5-10 parts), and cobalt (3-5 parts).
3. A process for preparing a high-capacity hydrogen storage alloy material according to claim 1, It is characterized in that The specific weight ratio of the raw materials in step 1 is: nickel (42-48 parts), samarium (6-7 parts), magnesium (16-18 parts), aluminum (12-14 parts), cerium (3-4 parts), manganese (6-7 parts), lanthanum (6-8 parts), and cobalt (3-4 parts).
4. A process for preparing a high-capacity hydrogen storage alloy material according to claim 2, It is characterized in that The specific weight ratio of the raw materials in step 1 is: nickel (45 parts), samarium (6 parts), magnesium (17 parts), aluminum (13 parts), cerium (4 parts), manganese (6 parts), lanthanum (7 parts), and cobalt (3 parts).
5. A process for preparing a high-capacity hydrogen storage alloy material according to claim 1, It is characterized in that The vacuum in step 2 is performed until the pressure in the reaction furnace does not exceed 10Pa, and then high-purity argon (≥99.999%) is filled to maintain the pressure in the furnace at 0.02-0.03MPa.
6. A process for preparing a high-capacity hydrogen storage alloy material according to claim 1, It is characterized in that The particle size of the crushed particles in step 4 is less than 150-200 mesh.
7. A process for preparing a high-capacity hydrogen storage alloy material according to claim 2, It is characterized in that In the step 5, the crushed alloy particles are placed in a heat treatment furnace, heated to 900° C., kept constant for 8 minutes, and then slowly cooled to room temperature at a rate of 30° C. / min.
Citation Information
Patent Citations
Rare earth-nickel base AB2 type hydrogen storage alloy material and preparation method
CN109868390A
Preparation method for hydrogen storage alloy material
CN110157951A
Chromium-containing lanthanum-calcium-magnesium-nickel series hydrogen storage alloy and preparation method and application thereof
CN118460882A
Hydrogen storage alloy and its production
JP1998088263A
